The Association between Obesity and Colorectal Cancer. (10th December 2012) - Whitlock, Kevin; Gill, Richdeep S.; Birch, Daniel W.; Karmali, Shahzeer
Abstract : Obesity has become a major issue for healthcare providers as its prevalence continues to increase throughout the world. The literature suggests that increased body mass index (BMI) is associated with the development of certain cancers such as colorectal cancer (CRC). Consequently, CRC surgeons are now encountering an increasing number of obese patients which may influence the technical aspects and outcomes of surgical treatment. For instance, obese patients present with greater comorbidities preoperatively, which adds increasing complexity and risks to surgical management. Recent literature also suggests that obesity may increase operating time and conversion rates to open colorectal surgery. Postoperative outcomes may also be influenced by obesity; however, this currently remains controversial. There is evidence that survival rates after CRC surgery are not influenced by obesity. In summary, obesity presents challenges to CRC surgeons, and further research will be needed to show how this important characteristic influences the outcomes for CRC patients.